Healthy Eating for Elders: Sixteen Savory Snacks - Jennifer B. Hillan (EDIS)
Here are some snack ideas that are not only easy to prepare, they are healthy too! Keep some of these choices handy for the next time you have the snacking urge. This is document FCS 8697-ENG, one in a series of the Department of Family, Youth and Community Sciences, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida, Gainesville, FL 32611. Publication date: February 2005.